A Combination Of Support Vector Machine And Inception-V3 In Face-Based Gender Classification - Doughlas Pardede; Wanayumini Wanayumini; Rika Rosnelly (Universitas Respati Yogyakarta, 2023)
Differences in human facial structures, especiallythose recorded in a digital image, can be used as an automaticgender comparison tool. This research utilizes machine learning using the support vector machine (SVM) algorithm to perform gender identification based on human facial images. The transfer learning technique using the Inception-v3 model is combined with the SVM algorithm to produce six models that implement polynomial, radial basis function (RBF), and sigmoid kernel functions. The results obtained are models with excellent performance, as seen from the lowest values of accuracy = 0.852, precision = 0.856, recall = 0.852, and the highest values of 0.957, 0.957, and 0.957. This combination also produces a model with excellent reliability, where the probability of overfitting or underfitting obtained is below 1%.